Kids who rule : the remarkable lives of five child monarchs - Cotter, Charis (Buffalo, NY : Distributed in the U.S.A. by Firefly Books, 2007)
Profiles five child monarchs, including Egyptian king Tutankhamun, Queen Christina of Sweden, the Last Emperor of China, Mary Queen of Scots, and the Dalai Lama of Tibet, describing their unique childhoods and their influence on their countries' history.
The immortal pharaoh : Tutankhamun of Egypt -- Queen on the run : Mary Queen of Scots -- The girl born to be king : Queen Christina of Sweden -- The make-believe emperor : Emperor Puyi of China -- Born (again) to rule (again) : the Dalai Lama of Tibet.
Includes bibliographical references (p. 115-116) and index.
Resource Links.
8.4
3-6
Keywords: Children -- Biography -- Juvenile literature; Kings and rulers -- Biography -- Juvenile literature; Children; Kings, queens, rulers, etc; Children -- Biography; Kings and rulers -- Biography